Diversity in Leadership Australian women, past and present - Damousi, Joy; Rubenstein, Kim; Tomsic, Mary (ANU Press, 2014)
While leadership is an over-used term today, how it is defined for women and the contexts in which it emerges remains elusive. Moreover, women are exhorted to exercise leadership, but occupying leadership positions has its challenges. Issues of access, acceptable behaviour and the development of skills to be successful leaders are just some of them.